Numerical and Experimental Investigations of a Micromixer with Chicane Mixing Geometry - Valentin Khaydarov; Ekaterina S. Borovinskaya; Wladimir Reschetilowski (Applied Sciences, 2018)
A micromixer is a new type of chemical engineering equipment used to intensify the mixing process. This article provides details on flow regimes in microchannels with a complex geometry, such as with chicane mixing geometry. Experiments involving water, ink, and a micro digital camera have determined both the micromixer’s initial mixing zone, and also the streamlines. Computational fluid dynamics (CFD) modelling helped identify the mechanism of stimulating effect; swirling and recirculation were identified as two special cases of the convective mixing process. To characterize the degree of mixing, a function of volume flow rate was proposed. A much higher degree of mixing in vortex flow compared to stratified flow was observed. The relationship between laminar flow and vortices shows a square-law dependence of pressure drop against the volume flow rate. The mixing cost and the mixing energy cost at Reynolds number of 50 are higher for the chicane micromixer than for micromixers without chicanes geometry.